Hello mr twiddle! - Blyton, Enid; Dell, Stephen (Award Publications Worksop, England, 2014)
Hello, Mr. Twiddle! by Enid Blyton is a lighthearted children$1 (Bs story about the amusingly absent-minded Mr. Twiddle, whose daily life is filled with comical mishaps and misunderstandings. Despite his good intentions, he often finds himself in ridiculous situations due to his forgetfulness and quirky ideas. Each chapter presents a new escapade, showcasing his interactions with friends, family, and neighbors, who are often bewildered by his antics. The book is filled with humor and charm, making it an enjoyable read for young audiences while highlighting themes of kindness and friendship amidst the chaos of everyday life.s